Polymeric Precipitation Inhibitor Based Supersaturable Self-microemulsifying Drug Delivery System of Canagliflozin: Optimization and Evaluation - Singh, Dilpreet; Tiwary, Ashok K.; Kang, Tejwant S.; Bedi, Neena (Current Drug Delivery, 2021)
Background: The present investigation attempts to optimize Supersaturable lipid based formulation (SS SMEDDS) of Biopharmaceutical Classification System (BCS) class IV drug canagliflozin (CFZ) and evaluating the oral bioavailability of the formulation. Methods: Preliminary screening revealed Poloxamer 188 to most effectively inhibit precipitation of CFZ after dispersion during in vitro supersaturation studies. Box Behnken Design was employed for designing different formulations, and various statistical analyses were done to select an appropriate mathematical model. The optimized formulation (OSS 1) was evaluated for in vitro drug release and ex vivo permeation studies to evaluate drug release and permeation rate. Pharmacokinetic studies have been carried out according to standard methodologies. Results: The optimized formulation (OSS 1) containing 781.1 mg SS SMEDDS and 2.24% w/w Poloxamer 188 was developed at a temperature of 60°C, which revealed nano-globule size with negligible aggregation. Isothermal titration calorimetry revealed the thermodynamic state of formed microemulsion with negative ΔG. The optimized formulation was observed to possess physical stability under different stress conditions and acceptable drug content. In vitro dissolution of optimized SS SMEDDS revealed a higher dissolution rate of CFZ as compared to native forms of CFZ. The permeability of CFZ from optimized SS SMEDDS across various excised segments of rat intestine was observed to be multifold higher as manifested by 2.05-fold higher Cmax and 5.64- fold higher AUC0-36h following oral administration to Wistar rats. Conclusion: The results could be attributed to substantial lymphatic uptake and P-glycoprotein substrate affinity of CFZ in SS SMEDDS investigated through chylomicron and P-glycoprotein inhibition approach, respectively.
Keywords: bioavailability